Mid-Gestational Enlargement of Fetal Thalami in Women Exposed to Methadone during Pregnancy - Schulson, Meredith; Liu, Anthony; Björkman, Tracey; Quinton, Ann; Mann, Kristy P.; Benzie, Ron; Peek, Michael; Nanan, Ralph (Frontiers in Surgery, 2014)
Methadone maintenance therapy is the standard of care in many countries for opioid-dependent women who become pregnant. Despite recent evidence showing significant neurodevelopmental changes in children and adults exposed to both licit and illicit substances in utero, data on the effects of opioids in particular remains scarce. The purpose of this study was to examine the effects of opiate use, in particular methadone, on various fetal cortical and biometric growth parameters in utero using ultrasound measurements done at 18-22 weeks gestation. Head circumference, bi-parietal diameter, lateral ventricle diameter, transcerebellar diameter, thalamic diameter, cisterna magna diameter, and femur length were compared between fetuses born to methadone-maintained mothers and non-substance using controls. A significantly larger thalamic diameter (0.05cm, p=0.01) was observed in the opiate-exposed group. Thalamic diameter/head circumference ratio was also significantly raised (0.03mm, p=0.01). We hypothesize here that the increase in thalamic diameter in opiate-exposed fetuses could potentially be explained by regional differences in opioid and serotonin receptor densities, an alteration in monoamine neurotransmitter systems, and an enhancement of the normal growth increase that occurs in the thalamus during mid-gestation.